Optimization of Polypropylene-Based Polymer Composites Fabrication Using Manual Forming for Automotive and Energy Applications - Ansyari, Muhammad Fadhillah; Utami, Yovi (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Polypropylene (PP)-based polymer composites are widely used in the automotive and energy industries due to their lightweight, strong, and corrosion-resistant properties. This study aims to optimize the fabrication process of polymer composites using the manual forming method, focusing on the effect of pressure and heating time on the material's mechanical properties. The materials used include polypropylene as the matrix and glass fibers as reinforcement. The process parameters varied include pressure (150–200 kgf/cm²) and heating time (10–20 minutes). Mechanical tests were conducted using a Universal Testing Machine (UTM) for tensile testing and an Izod Impact Tester for impact testing, following ASTM D638 and ASTM D256 standards. The results show that optimal pressure and heating time produced specimens with an average tensile strength of 35.3 MPa and impact energy absorption of 0.45 Joules. Although close to industry standards, uneven pressure distribution and air voids affected material homogeneity. In conclusion, the manual forming method can improve the quality of polymer composites for industrial applications, but further process parameter optimization is required to enhance material consistency.